2017
DOI: 10.1002/adhm.201601340
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Assembled Bilayer Cell Sheets of Stem Cells and Endothelial Cells Using Thermosensitive Hydrogels for Therapeutic Angiogenesis

Abstract: Although the coculture of multiple cell types has been widely employed in regenerative medicine, in vivo transplantation of cocultured cells while maintaining the hierarchical structure remains challenging. Here, a spatially assembled bilayer cell sheet of human mesenchymal stem cells and human umbilical vein endothelial cells on a thermally expandable hydrogel containing fibronectin is prepared and its effect on in vitro proangiogenic functions and in vivo ischemic injury is investigated. The expansion of hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Hydrogels could be obtained with different types of hydrophilic polymers (natural or synthetic). However, there may be some drawbacks, such as insufficient cell-anchorage cues, which can lead to minimal cell adhesion and spreading [99][100][101] or a decrease in cell viability in the case of cell encapsulation [102,103].…”
Section: Fn In Volumementioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels could be obtained with different types of hydrophilic polymers (natural or synthetic). However, there may be some drawbacks, such as insufficient cell-anchorage cues, which can lead to minimal cell adhesion and spreading [99][100][101] or a decrease in cell viability in the case of cell encapsulation [102,103].…”
Section: Fn In Volumementioning
confidence: 99%
“…Some remarkable studies dealing with Fn physical dispersion have been reported for alginate-based hydrogels [98,100,101,113]. For instance, Mosahebi et al investigated the addition of Fn in an alginate solution before physical gelation with Ca 2+ and its impact on nerve regeneration.…”
Section: Fn Physical Dispersionmentioning
confidence: 99%
“…Both of them contained abundant extracellular matrix (ECM) necessary for providing maximum strength and adherence to the host tissue surface . CSE includes cell culture in thermo-sensitive plates that develop compact cell sheets which detach with temperature drop (Jun et al, 2017). As a major advantage, this technology permits maintenance of growth factors, ECM proteins, and other bioactive cytokines because cells are detached spontaneously from the culture plates without the need for enzymatic procedures and proteolytic treatments.…”
Section: Stem Cell Sheet Engineering In the Endometrium Regenerationmentioning
confidence: 99%
“…This approach significantly increased proangiogenic activities by stimulating the release of nitric oxide and the expression of various types of proangiogenic factors (VE‐cadherin, vWF, and Tie‐2). Moreover, necrosis was significantly retarded after transplantation of cells into a region of hindlimb ischemia in mice, particularly in the group treated with the bilayer sheet . In another example, a human platelet lysate (PL) hydrogel was applied as a scaffold for delivery of MSCs and HUVECs to promote vascular regeneration.…”
Section: Type Of Polymers and Design Strategiesmentioning
confidence: 99%